Bruce L. Keenan, Book of Ordinances of the City of Wichita Published by Authority of a Resolution Adopted by the City Council April 24, 1899, under the Direction of Judiciary Committee and City Attorney, and Formally Authorized by Ordinance No. 1680 Page 45, Image 69 (1900) § 1 - (:unkn) unknown (General Publisher, 1899)
That any person, not an officer of the law in the execution of his duty, who shall in the city of Wichita, draw a pistol, revolver, knife, or any other deadly weapon upon another person shall upon conviction, be fined not less than twenty-five dollars nor more than one hundred dollars.
--
Keywords: BRANDISHING